“A life lived in cages”: strategies of containment in J.M. Coetzee’s Age of iron, Life & times of Michael K, Elizabeth Costello: eight lessons and “The poetics of reciprocity” - Van Heerden, Imke (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (English))--University of Stellenbosch, 2009.